Efficient Synthesis of a-Hydroxyacetophenone via Microwave Irradiation of a-Bromoacetophenone from Acetophenone - Xu, Haoshu; Wu, Xueping; Ding, Yun; Peng, Chengjun; Peng, Xinhua (Asian Journal of Chemistry, 2015)
Herein, we reported a new and efficient approach starting from acetophenone. In this work, a-hydroxyacetophenone was prepared under microwave irradiation of a-bromoacetophenone which was efficiently prepared by the use of HBr/H2O2 system.